CYBERBULLYING DALAM SOROTAN HADIS: Rekonstruksi Etika Bersosial Muslim Di Dunia Digital - Ayu, Ajeng; Ulfah Zakiyah; Abil Ash (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2026)
This study examines the hadith concerning the preservation of speech, which contains the Prophet Muhammad’s ﷺ instruction that a believer should speak good words or remain silent. The hadith is transmitted through multiple chains by Imam al-Bukhari, Muslim, al-Tirmidhi, Imam Malik, and Imam Ahmad, and is classified as authentic (ṣaḥīḥ) and acceptable for practice (maqbūl ma‘mūl bih). Using a qualitative approach with a descriptive-analytical method, this research analyzes the content of the hadith, the perspectives of classical scholars such as Ibn Ḥajar and Imam al-Ghazali, and its relevance to contemporary phenomena, particularly cyberbullying. The findings indicate that guarding one’s speech is an integral aspect of faith and worship, manifested through kind speech, self-restraint, and choosing silence when speech brings no benefit. This ethical principle plays a crucial role in fostering social harmony and preventing conflict. In the modern context, the concept of guarding the tongue is highly relevant as a foundation for digital communication ethics in addressing cyberbullying, which has significant negative psychological and social impacts on its victims. Therefore, internalizing the value of guarding one’s speech is essential for character development, strengthening social solidarity, and creating a healthy and dignified communication environment, both in real life and in digital spaces. This study is expected to contribute to the enrichment of hadith studies and to provide practical insights for responding to ethical challenges in contemporary digital communication.